The applicability of photobiomodulation: A integrative review (Research, Society and Development, 2024)
Objective: To investigate the effectiveness of laser therapy in periodontal clinical situations. Methodology: This is a integrative review study that sought to analyze the use of laser therapy in periodontal clinical conditions. For the literature search, articles available on Google Scholar and BVS were selected. The controlled descriptors used and listed by the Health Sciences Descriptors (DeCS) were: “laser therapy”, “Laser therapy”, “Non-surgical periodontal treatment” and “Chronic periodontitis”. The descriptors were crossed using the “AND” operator. The data were organized by content analysis, highlighting the most relevant points that the literature addresses on the subject, in addition to discussing the results of the studies with the literature. Results and discussion: Photodynamic therapy may be an alternative to control bone loss caused by periodontitis. Conclusion: Photobiomodulation has become a promising alternative in the field of dentistry, especially when combined with other treatments.